Effect of Levosimendan on Acute Decompensated Right Heart Failure in Patients With Connective Tissue Disease-Associated Pulmonary Arterial Hypertension - Qu, Chao; Feng, Wei; Zhao, Qi; Liu, Qi; Luo, Xing; Wang, Gang; Sun, Meng; Yao, Zhibo; Sun, Yufei; Hou, Shenglong; Zhao, Chunyang; Zhang, Ruoxi; et al. (Frontiers in Medicine, 2022)
Aims: Acute decompensated right heart failure (RHF) in chronic precapillary pulmonary hypertension is a condition often typified by a swiftly progressive syndrome involving systemic congestion that results from the impairment of the right ventricular filling and/or a reduction in the flow output of the right ventricular, which have been linked to a dismal prognosis of short duration. In spite of all this, there are quite limited therapeutic data regarding these acute incidents. This research sought to examine the effect of levosimendan on acute decompensated RHF in patients with connective tissue disease-associated pulmonary arterial hypertension (CTD-PAH). Methods: In this retrospective study, 87 patients confirmed CTD-PAH complicated acute decompensated RHF were included between November 2015 and April 2021. We collected biological, clinical, and demographic data, as well as therapy, from patients with acute decompensated RHF who needed levosimendan treatment in the cardiac care unit (CCU) for CTD-PAH. The patient was divided into two groups according to received levosimendan treatment. The information of patients between two groups was systematically compared in hospital and follow up. Results: Oxygen saturation of mixed venose blood (SvO2), estimated glomerular filtration rate (eGFR), 24-h urine output, and tricuspid annular plane systolic excursion (TAPSE) were discovered to be considerably elevated in the levosimendan cohort as opposed to the control cohort. The patients in the levosimendan cohort exhibited considerably reduced levels of C-reactive protein (CRP), white blood cell (WBC), troponin I, Creatinine, NT-proBNP, and RV diameter compared to the control cohort. A higher survival rate in hospital was observed in the levosimendan cohort. Conclusions: Levosimendan treatment could effectively improve acute decompensated RHF and systemic hemodynamics of CTD-PAH patients, with positive effects on survival in hospital, which may be an alternative treatment option for improving clinical short-term outcomes.